2024
DOI: 10.3390/vaccines12020127
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy among European Parents—Psychological and Social Factors Influencing the Decision to Vaccinate against HPV: A Systematic Review and Meta-Analysis

Teodora Achimaș-Cadariu,
Andrei Pașca,
Nicoleta-Monica Jiboc
et al.

Abstract: Background: Due to low adherence to HPV vaccination programs, the European region struggles with vaccination rates lower than 30% among the targeted population. The present report investigated various socio-demographic and psychological factors influencing European parents’ hesitancy towards vaccinating their children. Methods: As of September 2023, four databases were searched. After applying inclusion criteria, all articles comparing psychological and socio-demographic factors in parents who vaccinate or do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(489 reference statements)
0
1
0
Order By: Relevance
“…This information is also important to oral healthcare and public health professionals, as recent evidence has demonstrated that vaccine hesitancy (particularly related to HPV among pediatric patients) has been increasing in recent years despite strong evidence for the efficacy and safety of both the quadrivalent and nine-valent HPV vaccines [ 38 , 39 , 40 ]. In fact, other recent evidence has also documented the increase in vaccine hesitancy and skepticism about vaccine safety and efficacy over recent years among children, adolescents, and their parents [ 41 , 42 ]. One of the most effective and important methods for addressing vaccine hesitancy may be current information regarding HPV prevalence and infections among the patient population, such as that presented in this study, which demonstrates the relevance and importance of vaccination against high-risk oral HPV strains even in very young patients [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This information is also important to oral healthcare and public health professionals, as recent evidence has demonstrated that vaccine hesitancy (particularly related to HPV among pediatric patients) has been increasing in recent years despite strong evidence for the efficacy and safety of both the quadrivalent and nine-valent HPV vaccines [ 38 , 39 , 40 ]. In fact, other recent evidence has also documented the increase in vaccine hesitancy and skepticism about vaccine safety and efficacy over recent years among children, adolescents, and their parents [ 41 , 42 ]. One of the most effective and important methods for addressing vaccine hesitancy may be current information regarding HPV prevalence and infections among the patient population, such as that presented in this study, which demonstrates the relevance and importance of vaccination against high-risk oral HPV strains even in very young patients [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%